IMPLEMENTATION OF REGIONAL REGULATION NO. 1 OF 2022 CONCERNING ENREKANG REGENCY LIBRARY ORGANIZATION AND LITERACY MOVEMENT (International Conference on Social and Islamic Studies, 2022)
The purpose of this study was to analyze the implementation of Regional Regulation No. 1 of 2022 concerning Enrekang Regency Library Organization and Literacy Movement which was promulgated on March 17 2022, as well as to find out the supporting and inhibiting factors in the implementation process. This research is a qualitative descriptive study, which is located in Enrekang Regency, with data collection techniques through interviews, observation, and documentation. The results of the research show that the implementation of Regional Regulation Number 1 of 2022 has been carried out. The form of implementation of Regional Regulation Number 1 of 2022 is that the Library and Archives Service of Enrekang Regency has provided assistance to several Village/Wards for the establishment of a Village Library. The Enrekang Regency Library and Archives Service has also set up literacy corners and digital outlets in several villages/wards. Several obstacles, namely the involvement of the Community and Village Empowerment Service of Enrekang Regency in implementing Regional Regulation Number 1 of 2022 has not been implemented, and also the Library and Archives Service of Enrekang Regency is experiencing problems related to the lack of hardware that can support the establishment of digital outlets in every Village/Wards in the Regency Enrekang.